Redemption: a mimetic soteriology - Roumas, Nicholas (Orthodox Christianity and Contemporary Thought, 2025)
A bold, trailblazing investigation into soteriology, approached by way of Girardian mimetic theory and Eastern Orthodox theological reflectionRedemption: A Mimetic Soteriology brings French literary critic René Girard’s mimetic theory of human behavior together with a breadth of Christian approaches to redemption through the Cross. Girard’s mimetic understanding of sacrifice is drawn upon to illuminate biblical narratives about redemption as well as the theologies of Anselm of Canterbury, Peter Abelard, and Gregory of Nyssa. Nicholas Roumas shows by these readings that redemption can be understood as a reconfiguration of symbolic values with profound consequences for human relations and social organization. Redemption thus serves theologians as a basis for a new practical dogmatics.This exploration is a breath of fresh air in Orthodox theology, utilizing patristic and scriptural sources outside the framework of the predominant “neo-Patristic synthesis” and introducing an entirely new modern paradigm onto the Orthodox scene. For theologians of other traditions, Redemption contributes to the library of Girardian theologies its first Eastern Orthodox installment. For Girardians, it provides critique and refinement of many of Girard’s most nuanced views and gives due attention to overlooked and controversial aspects of his thought. For the lay reader, the book provides an accessible entry into the spirituality of the Cross through a lens that is both modern and traditional.Redemption provides a revitalizing infusion into contemporary Orthodox theological discourse. Its ideas will impact theology in the Orthodox Church and beyond for decades to come and are the basis for a paradigm shift in our understanding of redemption and its practical consequences. The lay reader and professional theologian alike will find novelty and utility in its ideas